PEMBERDAYAAN KELOMPOK CINTA LITERASI DAN MAHASISWA CINTA STATISTIK DALAM MENDUKUNG PROGRAM DIGITALISASI DI DESA REBO, KABUPATEN BANGKA - Dalimunthe, Desy Yuliana; Rozani, Muhammad; Kustiawan, Elyas; Febiola, Aulia (Jurnal Abdi Insani, 2024)
The village is a strategic position to support the success of community development programs. Currently, the concept of rural development is no longer limited to the agricultural sector and basic infrastructure but leads to the development of Information and Communication Technology. Rebo Village in general still has several things that have not been managed optimally, especially related to data literacy, such as having a low interest in reading and a lack of good understanding of the importance of improving literacy culture in the community. This service activity aims to explore the sources of potential (assets) owned by the community so that the community is able to solve the problems they face independently. The service scheme through socialization activities to partners aims to provide education about the importance of literacy to all village officials and all residents. This service activity focuses on the formation of a Literacy Love Group (KECIL) at the village level by involving statistical agents and statistical love students. This group can increase the added value of Rebo village towards an independent and creative village. This can be done by managing information and empowering the community. Based on the results of the analysis of the partner satisfaction questionnaire, 65.22% of participants answered that they agreed that the theme of the socialization activities presented was in accordance with the needs of partners and the rest, namely 34.78%, answered very agree. Based on the instrument of clarity and ease of understanding of the material presented by the resource persons, 73.91% answered yes and 26.09% answered strongly agree. In addition, this activity was also felt by partners to be very useful, as evidenced by 69.57% answering yes and 30.43% answering very agreeing. Meanwhile, several participants in the socialization activity gave positive and supportive suggestions for the progress and development of future activities. Based on the entire series of activities that have been carried out, it can be concluded that this service activity can provide its own benefits for partners, as evidenced by the results of the analysis of partner satisfaction questionnaire data in Rebo Village.